Asymmetric oxygen-containing tetradentate metal complex and its application

By using asymmetric oxygen-containing tetradent metal complex as catalysts, the problem of the reduction of activity of existing catalysts under high temperature conditions is solved, and polymer preparation with high molecular weight and high comonomer insertion rate is achieved, which significantly improves the performance of the polymer .

CN118027088BActive Publication Date: 2024-12-31BEOYI (SHANDONG) NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410160066.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-02
Publication Date
2024-12-31
Estimated Expiration
2044-02-02

AI Technical Summary

Technical Problem

The activity of existing olefin polymerization catalysts decreases under high temperature conditions, making it difficult to catalyze the preparation of polymers with high molecular weight and high comonomer content.

Method used

Asymmetric oxygen-containing tetradent metal complex is used as a catalyst to prepare polymers with high molecular weight and high comonomer insertion rate through copolymerization reaction with ethylene and α-olefins using their temperature resistance and high catalytic activity.

Benefits of technology

Maintaining high catalytic activity under high temperature conditions, the polymer obtained by catalyzing the copolymerization of ethylene and 1-octene is up to 38.9×104g/mol, and the molar insertion rate of 1-octene is up to 16.9%, which significantly improves the performance of the polymer .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure QLYQS_2
    Figure QLYQS_2
  • Figure QLYQS_3
    Figure QLYQS_3
Patent Text Reader

Abstract

The present invention relates to the technical field of olefin polymer catalysts, and in particular to an asymmetric oxygen-containing tetradentate metal complex and its application. The asymmetric oxygen-containing tetradentate metal complex has a structure shown in Formula I; in Formula I, R1, R2, R3, R4, R5, and R6 are independently selected from substituted or unsubstituted alkyl groups with 1 to 30 carbon atoms, cycloalkyl groups with 3 to 30 carbon atoms, or aryl groups with 6 to 30 carbon atoms; the substituent includes an alkyl group with 1 to 30 carbon atoms; X is selected from oxygen, sulfur or nitrogen; M is selected from the fourth subgroup transition metal; and n is 1 to 3. The complex structure provided by the present invention is easy to modify; as a catalyst, it has good temperature resistance and can maintain a high catalytic activity under high temperature conditions; it catalyzes the copolymerization reaction of ethylene and 1-octene to obtain a polymer product with a high molecular weight and a high comonomer insertion rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of olefin polymer catalysts, in particular to an asymmetric oxygen-containing tetradentate metal complex and application thereof. Background Art

[0002] Polyolefin products have many advantages such as abundant raw materials, low price, easy production and processing, good mechanical properties and superior performance. They have become the most widely used synthetic resin materials in production and life. The development level of the polyolefin industry directly represents the development level of a country's petrochemical industry and is an important part of the national economy and national defense strategy.

[0003] Olefin polymerization catalysts directly determine the internal structure and morphology of polyolefin products and are the core technology in the development of the polyolefin industry. Non-metallocene catalysts have a single active center, relatively high activity, strong tolerance of the central metal to heteroatoms, and the advantages of both ZN catalysts and metallocene catalysts. They can catalyze the homopolymerization and copolymerization of multiple series of olefin monomers, and achieve precise control of the molecular weight and internal morphology of polyolefin products, enriching the variety of polyolefin products and having very broad application prospects.

[0004] Enriching the types of olefin polymerization catalysts, improving the temperature resistance and activity of catalysts, and catalyzing the preparation of high molecular polymers and high monomer content polymers have become hot topics in this field. Summary of the invention

[0005] In view of this, the technical problem to be solved by the present invention is to provide an asymmetric oxygen-containing tetradentate metal complex and its application. The asymmetric oxygen-containing tetradentate metal complex provided by the present invention has good temperature resistance and high catalytic activity as a catalyst, and the obtained polymer has a high molecular weight and a high comonomer content.

[0006] The present invention provides an asymmetric oxygen-containing tetradentate metal complex having a structure shown in Formula I;

[0007]

[0008] In Formula I, R1, R2, R3, R4, R5, and R6 are independently selected from substituted or unsubstituted alkyl groups having 1 to 30 carbon atoms, cycloalkyl groups having 3 to 30 carbon atoms, or aryl groups having 6 to 30 carbon atoms; the substituents include alkyl groups having 1 to 30 carbon atoms;

[0009] X is selected from oxygen, sulfur or nitrogen;

[0010] M is selected from the fourth subgroup transition metal;

[0011] n is 1 to 3, such as 1, 2 or 3.

[0012] In some embodiments of the present invention, R1, R2, R3, R4, R5, and R6 are independently selected from substituted or unsubstituted alkyl groups having 1 to 12 carbon atoms, cycloalkyl groups having 3 to 15 carbon atoms, or aryl groups having 6 to 20 carbon atoms; the substituents include alkyl groups having 1 to 15 carbon atoms.

[0013] In some embodiments of the present invention, R1, R2, R3, R4, R5, and R6 are independently selected from methyl, ethyl, propyl, isopropyl, n-butyl, tert-butyl, adamantyl, carbazolyl, phenyl, cumyl, or triphenylmethyl.

[0014] In some embodiments of the present invention, the R1 is selected from H, methyl, ethyl, propyl, isopropyl, tert-butyl or phenyl.

[0015] In some embodiments of the present invention, R2 and R3 are independently selected from H or methyl.

[0016] In some embodiments of the present invention, R4, R5, and R6 are independently selected from H, methyl, ethyl, propyl, isopropyl, or tert-butyl.

[0017] In some embodiments of the present invention, the M is selected from titanium, zirconium or hafnium, more preferably zirconium or hafnium.

[0018] In some embodiments of the present invention, X is selected from oxygen or nitrogen.

[0019] In some embodiments of the present invention, the asymmetric oxygen-containing tetradentate metal complex is selected from one of Formulas 1 to 7;

[0020]

[0021]

[0022] The present invention has no particular limitation on the preparation method of the asymmetric oxygen-containing tetradentate metal complex. It can be prepared by various compound synthesis methods well known to those skilled in the art according to the compound structure, such as the method in the embodiments of the present invention.

[0023] The present invention also provides a polymer, which is prepared by using the above-mentioned asymmetric oxygen-containing tetradentate metal complex as a catalyst. Specifically, the polymer is prepared by copolymerization of ethylene and α-olefin; the copolymerization reaction uses the above-mentioned asymmetric oxygen-containing tetradentate metal complex as a catalyst, specifically, as a main catalyst.

[0024] The present invention also provides a method for preparing the above-mentioned polymer, comprising the following steps:

[0025] The polymer is prepared by copolymerization of ethylene and α-olefin; the copolymerization reaction uses the above-mentioned asymmetric oxygen-containing tetradentate metal complex as a catalyst. Specifically, the method comprises the following steps:

[0026] Under the action of a main catalyst and a co-catalyst, ethylene and α-olefin are copolymerized to obtain a polymer; the main catalyst is the asymmetric oxygen-containing tetradentate metal complex described above.

[0027] More specifically, the following steps are included:

[0028] Ethylene, α-olefin solution, main catalyst and co-catalyst are mixed and copolymerized to obtain a polymer; the main catalyst is the above-mentioned asymmetric oxygen-containing tetradentate metal complex.

[0029] In some embodiments of the present invention, the cocatalyst includes one or more of alkylaluminoxane, modified alkylaluminoxane, halogenated alkylaluminum and alkylaluminum; preferably includes methylaluminoxane or modified methylaluminoxane, and the modified methylaluminoxane can be generally commercially available, such as MMAO-7. In some embodiments of the present invention, the cocatalyst also includes a boron-containing substance, and the boron-containing substance is preferably triphenylcarbon-tetrakis(pentafluorophenyl)borate.

[0030] In some embodiments of the present invention, the molar ratio of Al in the co-catalyst to the metal element in the main catalyst is 1-6000:1, preferably 40-1000:1, more preferably 300-400:1, such as 400:1.

[0031] In some embodiments of the present invention, the molar ratio of boron in the co-catalyst to the metal element in the main catalyst is 0.1 to 2:1, preferably 1 to 2:1, and more preferably 1.5:1.

[0032] In some embodiments of the present invention, the α-olefin is selected from 1-octene. The solvent of the α-olefin solution is n-hexane. The concentration of the α-olefin solution is 0.1 to 5 mol / L, preferably 1 to 3 mol / L, and more preferably 1 mol / L.

[0033] In some embodiments of the present invention, the usage ratio of the main catalyst and the α-olefin solution is selected as 2-3 μmol: 350-550 mL, preferably 2.4-2.6 μmol: 380-520 mL, such as 2.5 μmol: 400 mL.

[0034] In some embodiments of the present invention, in the copolymerization reaction, the pressure of ethylene is 0.1 to 10 MPa, preferably 1 to 8 MPa, more preferably 2 to 6 MPa, and most preferably 2 to 4 MPa, such as 3.5 MPa.

[0035] In some embodiments of the present invention, the copolymerization reaction temperature is 60-210°C, preferably 120-180°C, more preferably 140-150°C, such as 140°C; the time is preferably 5-40 min, preferably 10-20 min, such as 10 min.

[0036] In some embodiments of the present invention, after the copolymerization reaction, the method further comprises:

[0037] The residual ethylene gas was released, the mixture was cooled, and the reaction mixture was poured into a mixed solution of hydrochloric acid and ethanol. After stirring, the mixture was filtered and dried to obtain a polymer.

[0038] The cooling is natural cooling to 40°C.

[0039] The concentration of the hydrochloric acid is 2-4 mol / L, specifically 3 mol / L.

[0040] The volume ratio of the hydrochloric acid to the ethanol is 1:1.

[0041] The stirring time is 3 to 7 minutes.

[0042] The present invention has no particular limitation on the sources of the raw materials used above, and they can be generally commercially available.

[0043] The asymmetric oxygen-containing tetradentate metal complex provided by the present invention has a structure that is easy to modify; as a catalyst, it has good temperature resistance and can maintain a high catalytic activity under high temperature conditions; it catalyzes the copolymerization of ethylene and 1-octene to obtain a polymer product with a high molecular weight and a high comonomer insertion rate. Experimental results show that the molecular weight of the polymer obtained by the copolymerization of ethylene and 1-octene catalyzed by the asymmetric oxygen-containing tetradentate metal complex provided by the present invention is as high as 38.9×10 4 g / mol, and the molar insertion rate of 1-octene was the highest at 16.9%. DETAILED DESCRIPTION

[0044] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0045] Example 1

[0046] The ligand having the structure shown in Formula II was prepared according to the following synthetic route:

[0047]

[0048] In the ligand of the structure shown in formula II, the alkyl groups in R1, R2, R3, R4, R5, and R6 are independently selected from C1 to C12 alkyl groups. Specifically, the ligand of the structure shown in formula II is selected from compounds of formulas L1 to L6;

[0049]

[0050] Preparation of ligand L1:

[0051]

[0052] Under room temperature, the corresponding compound of formula A (1.0 eqv) was dissolved in 500 mL of dry acetonitrile, the system was replaced with a nitrogen atmosphere, KOH (1.5 eqv) solid was added thereto, and then benzyl chloride (1.5 eqv) was added, and the reaction was refluxed for 8 h, the reaction was stopped, filtered, and the acetonitrile was removed by rotary evaporation, 200 mL of ether and 250 mL of water were added, the organic phase was separated, and then the aqueous phase was extracted with ether for 3 times, the organic phases were combined and retained, dried over anhydrous magnesium sulfate, filtered, and the solvent was removed by rotary evaporation to obtain a substantially equivalent raw material protected by a benzyl group (as shown in formula B);

[0053] Under nitrogen protection, dimethylformal (10.0 eqv) and phosphorus pentoxide (3.5 eqv) were added to a Schlenk bottle in sequence, and dichloromethane was added as a solvent. The mixture was cooled to 0°C, and a dichloromethane solution of 2-bromo-5-methylphenol (Formula C, 1.0 eqv) was added dropwise to the above system using a dropping funnel. The addition was completed in 20 min, and the mixture was heated to room temperature and the reaction was continued for 1.5 h. At this time, the system was light yellow, and the reaction was stopped. The supernatant was poured out, and a 10% NaOH solution (100 mL) was added for separation. The organic phase was retained, and anhydrous magnesium sulfate was added for drying. The mixture was filtered and the solvent was removed by rotary evaporation to obtain a substantially equivalent raw material protected by the MOM group (as shown in Formula D);

[0054] Add the compound of formula B (1.0 eqv) and dry THF (150 mL) into a Schlenk bottle, cool to -78°C, drip 1.6 mol / L n-butyl lithium (1.1 eqv) into the above system, drip it all over in 0.5 h, keep the temperature and continue to react for 40 min, drip triisopropyl borate (1.5 eqv) into the above system, drip it all over in 20 min, warm to room temperature and continue to react for 1.5 h, add water (150 mL) to quench the reaction, separate the liquids and retain the organic phase, extract the aqueous phase with ethyl acetate 3 times, combine the organic phases, dry over anhydrous magnesium sulfate, filter, and remove the solvent by rotary evaporation to obtain a white solid, which is recrystallized from dichloromethane to obtain a white powder;

[0055] Then, under nitrogen protection, the intermediate product (1.20 eqv) obtained in the previous step was added to a Schlenk bottle, and then the compound of formula D (1.0 eqv), sodium carbonate (1.66 eqv), water (30 mL), and ethylene glycol dimethyl ether (90 mL) were added in sequence, the system was replaced with a nitrogen atmosphere, tetrakistriphenylphosphine palladium (0.05 eqv) was added, a reflux condenser was connected, and the reaction was heated under reflux for 36 hours, the reaction was stopped, cooled to room temperature, ethyl acetate was added to quench the reaction, the organic phase was retained, the aqueous phase was extracted 3 times with ethyl acetate, the organic phases were combined, dried over anhydrous magnesium sulfate, filtered, and the solvent was removed by rotary evaporation to obtain a reddish brown oily liquid, which was recrystallized with a mixed solvent of petroleum ether: acetonitrile = 1:20 (volume ratio) to obtain a pure white powder (as shown in formula E);

[0056] The compound of formula E (1.0 eqv) was added to a Schlenk bottle, and THF (60 mL), ethanol (100 mL), and concentrated hydrochloric acid (10 mL) were added thereto in sequence. A reflux condenser was connected, and the system was replaced with a nitrogen atmosphere. The system was heated under reflux for 3 h. A large amount of precipitate was precipitated in the system. The reaction was stopped and cooled to room temperature. The filter cake was obtained by filtration. The crude product was dissolved in dichloromethane, and the insoluble matter was removed by filtration. The filtrate solvent was removed by rotary evaporation, and the filtrate was recrystallized with a mixed solvent of ethyl acetate: petroleum ether = 1:20 (volume ratio) to obtain a pure white powder (as shown in formula F);

[0057] Under nitrogen protection, add the compound of formula F (1.0 eqv) and dry ether (150 mL) in sequence to a Schlenk bottle, cool to 0°C, add n-butyl lithium (2.0 eqv) solution dropwise thereto, and drip for 30 minutes. After the dripping is complete, warm to room temperature and continue to react for 3 hours; add the above reaction system dropwise to 1,3-dibromopropane (5.0 eqv), and continue to react at room temperature for 8 hours; remove volatile components under vacuum conditions, increase to 80°C and continue to extract for 1.5 hours, cool to room temperature, add 30 mL of dry ether, filter to remove inorganic salts, remove volatile components, and separate by column chromatography to obtain a compound of formula G;

[0058] Under nitrogen protection, add the compound of formula G (1.0 eqv) and dry ether (150 mL) in sequence to a Schlenk bottle, cool to 0°C, add n-butyl lithium (2.0 eqv) solution dropwise thereto, and drip for 30 minutes. After the dripping is complete, warm to room temperature and continue to react for 3 hours; add the above reaction system dropwise to 2-bromo-4-methylphenol (1.1 eqv), and continue to react at room temperature for 8 hours; remove volatile components under vacuum conditions, increase to 80°C and continue to extract for 1.5 hours, cool to room temperature, add 30 mL of dry ether, filter to remove inorganic salts, remove volatile components, and separate by column chromatography to obtain a compound of formula H;

[0059] Under nitrogen protection, the compound of formula H (1.0 eqv) is completely dissolved in 20 mL of tetrahydrofuran (THF), and slowly added dropwise to a reaction system containing iodine (0.01 eqv) and metal magnesium powder (1.0 eqv), and reacted at 40°C for 2 hours to obtain a compound of formula I of diaryl magnesium bromide Grignard reagent; after the reaction is completed, it is cooled to room temperature and slowly added to a tetrahydrofuran (THF) solution of 3',5'-dimethyl-3'-tert-butyl-1,1'-biphenyl-2-pentanone, i.e., a substituted biphenyl ketone compound of formula J (1.0 eqv), and reacted at 40°C for 2 hours. After the reaction is completed, it is hydrolyzed with 0.1 mol / L hydrochloric acid and separated, the organic phase is collected and washed with saturated sodium carbonate aqueous solution, dried with anhydrous sodium sulfate to remove water, filtered and the filtrate is collected. Finally, the filtrate is subjected to rotary evaporation to obtain a crude product, which is recrystallized from ethyl acetate to obtain a compound of formula K;

[0060] In a stainless steel reactor, add compound K (1.0 eqv), palladium carbon (0.05 eqv), acetic acid (0.02 eqv), ethyl acetate (30 mL) and ethanol (30 mL) in sequence, pressurize hydrogen into the stainless steel reactor, set the pressure to 6 MPa, heat to 60°C, react for 12 h, stop the reaction, release the pressure, replace with nitrogen atmosphere, cool to room temperature, filter, remove the solvent by rotary evaporation, and recrystallize with ethyl acetate to obtain ligand L1 (compound L).

[0061] Example 2

[0062] Preparation of asymmetric oxygen-containing tetradentate metal complex (Formula 1):

[0063] Under nitrogen atmosphere, weigh ZrCl4 powder (1.0eqv) in a Schlenk bottle, add toluene (80mL), place on a stirrer and stir rapidly for 30min to disperse the powder particles evenly in the bottle, cool to -35°C, pour ligand L1 (compound of formula L, 1.0eqv) powder into the above system in batches, sprinkle the powder on the bottle wall with toluene (20mL), continue stirring for 2min, then drip methylmagnesium bromide ether solution (4.1eqv) into the above system, drip it after 2min, stop cooling, and slowly increase the temperature. When it reaches room temperature, the suspension in the bottle will gradually dissolve and become semi-transparent, and the color will change from white to gray; continue to react at room temperature for 1 hour, use an oil pump to vacuum remove the toluene solvent, add toluene (15 mL) to dissolve the complex, filter out insoluble matter, quickly stir the filtrate, add n-hexane dropwise until precipitation is just produced, freeze to -25°C for 1 hour, precipitate more white crystalline solid, filter to obtain colorless crystalline metal complex, place it in a 60°C oil bath, vacuum for 3 hours to remove the solvent, and obtain complex formula 1 (compound M).

[0064] Example 3

[0065] Preparation of asymmetric oxygen-containing tetradentate metal complex (Formula 3):

[0066] Under nitrogen atmosphere, weigh HfCl4 powder (1.0eqv) in a Schlenk bottle, add toluene (80mL), place on a stirrer and stir rapidly for 30min to disperse the powder particles evenly in the bottle, cool to -35°C, pour ligand L1 (compound of formula L, 1.0eqv) powder into the above system in batches, sprinkle the powder on the bottle wall with toluene (20mL), continue stirring for 2min, then drip methylmagnesium bromide ether solution (4.1eqv) into the above system, drip it in 2min, stop cooling, and slowly Slowly warm to room temperature, the suspension in the bottle will gradually dissolve and become semi-transparent, and the color will change from white to gray; continue to react at room temperature for 1 hour, use an oil pump to vacuum remove the toluene solvent, add toluene (15 mL) to dissolve the complex, filter out insoluble matter, quickly stir the filtrate, add n-hexane dropwise until precipitation occurs, freeze to -25°C for 1 hour, precipitate more white crystalline solid, filter to obtain colorless crystalline metal complex, place it in a 60°C oil bath, vacuum for 3 hours to remove the solvent, and obtain complex 3.

[0067] Asymmetric oxygen-containing tetradentate metal complexes of formula 1 to 7 were prepared according to the methods of Example 2 and Example 3. The yields, yields and elemental analysis results are as follows:

[0068] Metal complex with the structure shown in formula 1 (Cat. 1), yield: 9.33%, elemental analysis: measured (calculated) C: 71.99 (71.99) H: 6.87 (6.87) O: 5.98 (5.98);

[0069] Metal complex with the structure shown in formula 2 (Cat. 2), yield: 8.93%, elemental analysis: measured (calculated) C: 68.56 (68.57) H: 6.57 (6.58) O: 4.18 (4.18) S: 8.36 (8.37);

[0070] Metal complex with the structure shown in formula 3 (Cat. 3), yield: 10.11%, elemental analysis: measured (calculated) C: 64.36 (64.34) H: 6.15 (6.14) O: 8.72 (8.72);

[0071] Metal complex with the structure shown in formula 4 (Cat. 4), yield: 9.44%, elemental analysis: measured (calculated) C: 72.25 (72.25) H: 7.00 (7.01) O: 8.55 (8.55);

[0072] Metal complex with the structure shown in Formula 5 (Cat.5), yield: 9.39%, elemental analysis: measured (calculated) C: 71.71 (71.72) H: 6.73 (6.72) O: 8.89 (8.89);

[0073] Metal complex with the structure shown in formula 6 (Cat. 6), yield: 8.93%, elemental analysis: measured (calculated) C: 73.99 (73.99) H: 7.97 (7.97) O: 7.44 (7.44);

[0074] The metal complex with the structure shown in Formula 7 (Cat.7), yield: 9.03%, elemental analysis: measured (calculated) C: 74.54 (74.53) H: 8.27 (8.27) O: 7.08 (7.09).

[0075] Example 4

[0076] Catalytic copolymerization of ethylene and 1-octene:

[0077] The polymerization reaction was carried out in a 500mL stainless steel autoclave. The autoclave equipped with mechanical stirring was heated to 150°C, vacuumed for 1h, the system was adjusted to the required temperature conditions for polymerization, 0.1MPa of ethylene gas was charged, a certain amount of modified methylaluminoxane (MMAO-7) and a certain concentration of α-olefin (1-octene) in n-hexane solution (volume 400mL) were added to the autoclave, and the temperature was kept constant for a period of time, 3.5MPa of ethylene gas was introduced, and ethylene was allowed to reach a dissolution equilibrium for 10min, and then the main catalyst was added (when adding a boron co-catalyst, it was necessary to mix and shake with the main catalyst in advance and stand for 5min; the molar ratio of boron in the boron co-catalyst to the metal element in the main catalyst was 1.5:1), and stirred for a period of time. After the polymerization reaction was completed, the residual ethylene gas was discharged, and the mixture was naturally cooled to 40°C, and the reactor was opened. The obtained polymerization reaction mixture was poured into a mixed solution of 3mol / L hydrochloric acid and ethanol in a volume ratio of 1:1, stirred for 5min, filtered, and dried in a vacuum oven to obtain a polymer.

[0078] Polymerization conditions: The main catalysts are asymmetric oxygen-containing tetradentate metal complexes of formulas 1 to 7, with an amount of 2.5 μmol; the co-catalyst is MMAO-7, Al / M (molar ratio) = 400:1; the concentration of 1-octene solution is 1 mol / L; the polymerization pressure is 3.5 MPa, the polymerization temperature is 140°C, and the polymerization time is 10 min; a Molecular weight and molecular weight distribution were measured by GPC; b Depend on 13 Measured by CNMR.

[0079] The polymer prepared in Example 4 was weighed, its molecular weight and molecular weight distribution were measured, and the monomer insertion rate was tested by high temperature carbon spectrum. The test results are shown in Table 1.

[0080] Table 1 Relevant data of polymer obtained in Example 4

[0081]

[0082]

[0083] As can be seen from Table 1, the asymmetric oxygen-containing tetradentate metal complex provided by the present invention is used as a catalyst for catalyzing the copolymerization of ethylene and 1-octene, and has high activity, high product yield, high product molecular weight, and high 1-octene molar insertion rate; the hafnium catalyst is more active than the zirconium catalyst.

[0084] The present invention provides a novel asymmetric oxygen-containing tetradentate fourth-group metal complex, which has good temperature tolerance and can maintain high catalytic activity at 140°C. The complex is used as a main catalyst to catalyze the copolymerization of ethylene and 1-octene, with high activity, and high molecular weight and comonomer insertion rate of the polymer. Experimental results show that the molecular weight of the polymer obtained by the copolymerization of ethylene and 1-octene catalyzed by the complex provided by the present invention is as high as 38.9×10 4 g / mol, and the molar insertion rate of 1-octene was the highest at 16.9%.

[0085] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. An asymmetric oxygen-containing tetradentate metal complex having a structure shown in Formula I; Formula I; In Formula I, R1, R2, R3, R4, R5, and R6 are independently selected from H, substituted or unsubstituted alkyl groups having 1 to 30 carbon atoms, cycloalkyl groups having 3 to 30 carbon atoms, or aryl groups having 6 to 30 carbon atoms; the substituent is an alkyl group having 1 to 30 carbon atoms; X is selected from oxygen or sulfur; M is selected from the fourth subgroup transition metal; n is 1~3.

2. The asymmetric oxygen-containing tetradentate metal complex according to claim 1, characterized in that: R1, R2, R3, R4, R5 and R6 are independently selected from substituted or unsubstituted alkyl groups having 1 to 12 carbon atoms, cycloalkyl groups having 3 to 15 carbon atoms or aryl groups having 6 to 20 carbon atoms; the substituent is an alkyl group having 1 to 15 carbon atoms.

3. The asymmetric oxygen-containing tetradentate metal complex according to claim 1, characterized in that: R1, R2, R3, R4, R5, and R6 are independently selected from methyl, ethyl, propyl, n-butyl, tert-butyl, adamantyl, phenyl, or cumyl.

4. The asymmetric oxygen-containing tetradentate metal complex according to claim 3, characterized in that: The propyl group is isopropyl group.

5. The asymmetric oxygen-containing tetradentate metal complex according to claim 1, characterized in that: The R1 is selected from H, methyl, ethyl, propyl, tert-butyl or phenyl; The R2 and R3 are independently selected from H or methyl.

6. The asymmetric oxygen-containing tetradentate metal complex according to claim 5, characterized in that: The propyl group is isopropyl group.

7. The asymmetric oxygen-containing tetradentate metal complex according to claim 1, characterized in that: The R4, R5 and R6 are independently selected from H, methyl, ethyl, propyl or tert-butyl.

8. The asymmetric oxygen-containing tetradentate metal complex according to claim 7, characterized in that: The propyl group is isopropyl group.

9. The asymmetric oxygen-containing tetradentate metal complex according to claim 1, characterized in that: The asymmetric oxygen-containing tetradentate metal complex is selected from one of Formula 1 to Formula 7; Formula 1; Formula 2; Formula 3; Formula 4; Formula 5; Formula 6; Formula 7.

10. A method for preparing a polymer, comprising the following steps: The polymer is prepared by copolymerizing ethylene and α-olefin; The copolymerization reaction uses the asymmetric oxygen-containing tetradentate metal complex described in any one of claims 1 to 9 as a catalyst.

11. The preparation method according to claim 10, characterized in that: The preparation method comprises: Under the action of the main catalyst and the co-catalyst, ethylene and α-olefin are copolymerized to obtain a polymer; The main catalyst is an asymmetric oxygen-containing tetradentate metal complex as described in any one of claims 1 to 9 as a catalyst.